2012
DOI: 10.6064/2012/703675
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropathology of Autism

Abstract: Autism is a behaviorally defined neurodevelopmental disorder that affects over 1% of new births in the United States and about 2% of boys. The etiologies are unknown and they are genetically complex. There may be epigenetic effects, environmental influences, and other factors that contribute to the mechanisms and affected neural pathway(s). The underlying neuropathology of the disorder has been evolving in the literature to include specific brain areas in the cerebellum, limbic system, and cortex. Part(s) of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 120 publications
(152 reference statements)
2
49
0
1
Order By: Relevance
“…Our study provides novel evidence that altered expression of parvalbumin is another neuropathological feature of the cerebellum in individuals with ASD. It is well established that the cerebellum is a major locus of neuropathology in autism [reviewed in Blatt, ; Fatemi et al, ]. Early cerebellar damage/injury has been reported to be a very high risk factor for ASD [Limperopoulos et al, ; see Wang, Kloth, & Badura, for review].…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides novel evidence that altered expression of parvalbumin is another neuropathological feature of the cerebellum in individuals with ASD. It is well established that the cerebellum is a major locus of neuropathology in autism [reviewed in Blatt, ; Fatemi et al, ]. Early cerebellar damage/injury has been reported to be a very high risk factor for ASD [Limperopoulos et al, ; see Wang, Kloth, & Badura, for review].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a fragile X mental retardation 1 ( FMR1 ) gene KO model of fragile X syndrome, the total number of neurons, including GABA‐immunopositive interneurons in the BLA, was unaffected. Similarly, human studies of autistic children have shown little morphological alterations in the BLA compared with developmentally typical children (for review see Blatt, ). However, there appears to be a significant decrease in the total number of BLA inhibitory synaptic connections, indicating aberrant circuit development (Olmos‐Serrano et al, ).…”
Section: Gabaergic Circuit Dysfunction Within the Blamentioning
confidence: 98%
“…Altered neurodevelopment during early pregnancy represents the neuropathological cause of ASD [53,54]. Postmortem studies have unveiled neuroanatomical and cytoarchitectonic abnormalities in the cerebellum, inferior olivary complex, deep cerebellar nuclei, hippocampus, amygdala, entorhinal cortex, fusiform gyrus, and anterior and posterior cingulate cortex, with thinner cortical minicolumns, excessive growth of the frontal lobes, and excessive dendritic spine density [55]. These abnormalities are suggestive of derangements occurring during the first/second trimester of pregnancy, namely reduced programmed cell death and/or increased cell proliferation, altered cell migration, abnormal cell differentiation with reduced neuronal body size, abnormal neurite sprouting, and pruning that result in atypical cell-cell wiring.…”
Section: Autism Spectrum Disorder: Clinical Traits Neuropsychologicamentioning
confidence: 99%